PROCESSING OF MEDICAL MASK WASTE IN GORONTALO CITY DURING THE COVID-19 PANDEMIC - Nur Ayini S. Lalu; Moh. Rivai Nakoe; Julianty Akuba; Laksmyn Kadir (International Journal of Health Science & Medical Research, 2023)
The disposal of disposable masks has raised concerns among environmentalists. Disposable medical mask waste is currently easy to find because people throw it away everywhere in intact condition. When people throw away masks carelessly, it is difficult to distinguish the use of shows by people with excellent or diseased health conditions. The problem in this research is the improper management of medical masks. This research method aims to analyze the frequency of using masks when leaving the house and the practice of processing medical mask waste used by the people of Gorontalo City. This type of research is quantitative with a cross-sectional design and analytic descriptive method. The population in this study were all people living in the City of Gorontalo in 2 sub-districts, namely Kota Timur and Kota Utara, with a sample size of 379 samples from the City of East and 377 representatives from the City of North. The results showed that the processing of medical masks in Gorontalo City during the Covid-19 Pandemic was not on target; this was evidenced by the processing of medical mask waste in Kota Timur District, which was disposed of carelessly as much as 36.5%, while medical mask waste was processed by cutting and 16.7% were burnt for the East Kota sub-district and 15.9% processed and reused. This study concluded that in the processing of medical masks in Gorontalo City during the Covid-19 pandemic for the East City District, many were still disposed of carelessly. In contrast, most medical mask users were washed and reused for the North City District. In comparison, for the North sub-district, it was 4.2%; even out of the 377 respondents surveyed, 361 medical mask users washed and reused. This is very worrying for environmental experts because the repeated use of medical masks will particularly impact oral health.Keywords: Processing; Waste; Medical mask.